Implementation of Health Protocols for Seller at Oebobo Traditional Market - Fatma Muktya Djawas; Masrida Sinaga; Amelya B Sir (Universitas Nusa Cendana, 2023)
Oebobo Traditional Market is one of the traditional markets located in district of Oebobo, the district with the highest number of COVID-19 cases in Kupang, with 823 cases. The implementation of health protocols is one of the essential steps to prevent the COVID-19 virus that is easy to spread, especially through droplets that come out when someone talks, coughs, or sneezes. This study aimed to describe the implementation of health protocols for sellers in the Oebobo Traditional Market. This research was descriptive quantitative research. Respondents in this study were sellers in Oebobo Traditional Market, and the respondents were 80 people. The instrument in this study was a questionnaire. The analytical technique in this study is descriptive analysis to see the description of the implementation of health protocols on sellers at Oebobo Traditional Market. The results showed that 8% of respondents always used masks, 54% always washed their hands, 8% always kept their distance, and 100% did not use plastic barriers between sellers and buyers. The cause for not implementing health protocols is because there is a bad feeling if traders have to ask to use masks or keep a distance. They also have difficulty breathing or communicating, maintaining a distance because of the narrow place, lack of facilities for washing hands such as soap or water, and lack of supervision by officers. It is recommended that the sellers better comply with the health protocols set by the government and can improve to control the implementation of health protocols at Oebobo Traditional Market.